Using Population Descriptors in Genetics and Genomics Research: A New Framework for an Evolving Field - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2023)
Genetic and genomic information has become far more accessible, and research using human genetic data has grown exponentially over the past decade. Genetics and genomics research is now being conducted by a wide range of investigators across disciplines, who often use population descriptors inconsistently and/or inappropriately to capture the complex patterns of continuous human genetic variation. In response to a request from the National Institutes of Health, the National Academies assembled an interdisciplinary committee of expert volunteers to conduct a study to review and assess existing methodologies, benefits, and challenges in using race, ethnicity, ancestry, and other population descriptors in genomics research. The resulting report focuses on understanding the current use of population descriptors in genomics research, examining best practices for researchers, and identifying processes for adopting best practices within the biomedical and scientific communities.
Keywords: Health and Medicine; Behavioral and Social Sciences

Oversight and Review of Clinical Gene Transfer Protocols: Assessing the Role of the Recombinant DNA Advisory Committee - Institute of Medicine (The National Academies Press, 2014)
Gene transfer research is a rapidly advancing field that involves the introduction of a genetic sequence into a human subject for research or diagnostic purposes. Clinical gene transfer trials are subject to regulation by the U.S. Food and Drug Administration (FDA) at the federal level and to oversight by institutional review boards (IRBs) and institutional biosafety committees (IBCs) at the local level before human subjects can be enrolled. In addition, at present all researchers and institutions funded by the National Institutes of Health (NIH) are required by NIH guidelines to submit human gene transfer protocols for advisory review by the NIH Recombinant DNA Advisory Committee (RAC). Some protocols are then selected for individual review and public discussion. Oversight and Review of Clinical Gene Transfer Protocols provides an assessment of the state of existing gene transfer science and the current regulatory and policy context under which research is investigated. This report assesses whether the current oversight of individual gene transfer protocols by the RAC continues to be necessary and offers recommendations concerning the criteria the NIH should employ to determine whether individual protocols should receive public review. The focus of this report is on the standards the RAC and NIH should use in exercising its oversight function. Oversight and Review of Clinical Gene Transfer Protocols will assist not only the RAC, but also research institutions and the general public with respect to utilizing and improving existing oversight processes.
Keywords: Health and Medicine

The Economics of Genomic Medicine: Workshop Summary - Institute of Medicine (The National Academies Press, 2013)
The sequencing of the human genome and the identification of links between specific genetic variants and diseases have led to tremendous excitement over the potential of genomics to direct patient treatment toward more effective or less harmful interventions. Still, the use of whole genome sequencing challenges the traditional model of medical care where a test is ordered only when there is a clear indication for its use and a path for downstream clinical action is known. This has created a tension between experts who contend that using this information is premature and those who believe that having such information will empower health care providers and patients to make proactive decisions regarding lifestyle and treatment options. In addition, some stakeholders are concerned that genomic technologies will add costs to the health care system without providing commensurate benefits, and others think that health care costs could be reduced by identifying unnecessary or ineffective treatments. Economic models are frequently used to anticipate the costs and benefits of new health care technologies, policies, and regulations. Economic studies also have been used to examine much more specific issues, such as comparing the outcomes and cost effectiveness of two different drug treatments for the same condition. These kinds of analyses offer more than just predictions of future health care costs. They provide information that is valuable when implementing and using new technologies. Unfortunately, however, these economic assessments are often limited by a lack of data on which to base the examination. This particularly affects health economics, which includes many factors for which current methods are inadequate for assessing, such as personal utility, social utility, and patient preference. To understand better the health economic issues that may arise in the course of integrating genomic data into health care, the Roundtable on Translating Genomic-Based Research for Health hosted a workshop in Washington, DC, on July 17-18, 2012, that brought together economists, regulators, payers, biomedical researchers, patients, providers, and other stakeholders to discuss the many factors that may influence this implementation. The workshop was one of a series that the roundtable has held on this topic, but it was the first focused specifically on economic issues. The Economics of Genomic Medicine summarizes this workshop.
Keywords: Health and Medicine

Refining Processes for the Co-Development of Genome-Based Therapeutics and Companion Diagnostic Tests: Workshop Summary - Institute of Medicine (The National Academies Press, 2014)
Many drug developers have examined new strategies for creating efficiencies in their development processes, including the adoption of genomics-based approaches. Genomic data can identify new drug targets for both common and rare diseases, can predict which patients are likely to respond to a specific treatment, and has the potential to significantly reduce the cost of clinical trials by reducing the number of patients that must be enrolled in order to demonstrate safety and efficacy. A key component of the approval of targeted therapeutics is the ability to identify the population of patients who will benefit from treatment, and this has largely hinged on the co-development and co-submission to the FDA of a companion diagnostic test.The co-development process, or the development of the test and drug for the simultaneous submission to FDA, has led to a major alteration in the way that drugs are being developed, with traditionally separate entities—pharmaceutical and diagnostic companies—now working in close collaboration. Refining Processes for the Co-Development of Genome-Based Therapeutics and Companion Diagnostic Tests is the summary of a workshop held by the Roundtable on Translating Genomic-Based Research for Health on February 27, 2013 to examine and discuss challenges and potential solutions for the codevelopment of targeted therapeutics and companion molecular tests for the prediction of drug response. Prior to the workshop, key stakeholders, including laboratory and medical professional societies, were individually asked to provide possible solutions to resolve the concerns raised about co-development of companion diagnostic tests and therapies. Workshop speakers were charged with addressing these solutions in their presentations by providing insight on (1) whether the proposed solutions address the problems described, (2) whether there are other solutions to propose, and (3) what steps could be taken to effectively implement the proposed solutions.
Keywords: Health and Medicine

Improving Diversity of the Genomics Workforce: Proceedings of a Workshop—in Brief - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2022)
In 2020, as part of its strategic planning initiative, the Roundtable on Genomics and Precision Health of the National Academies of Sciences, Engineering, and Medicine decided to explore four action-oriented focus areas for its activities over the coming three to five years: driving innovation, shaping the policy dialogue, spurring the adoption of tools and approaches, and achieving equity. The roundtable began its exploration of the fourth thematic area - achieving equity in genomics and precision health - by holding a public workshop on October 5, 2021. The workshop, Improving Diversity of the Genomics Workforce, examined the current state of diversity of the genetics and genomics workforce; the structural and social factors associated with the lack of workforce diversity; the impact of diversity in the workforce on access to genetic services and patient outcomes; and possible actions that could lead to a more diverse, equitable, and inclusive genomics workforce. This Proceedings of a Workshop-in Brief highlights the presentations and discussions that occurred during the workshop.
Keywords: Health and Medicine

Realizing the Potential of Genomics across the Continuum of Precision Health Care: Proceedings of a Workshop - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2023)
The National Academies Roundtable on Genomics and Precision Health, in collaboration with the National Cancer Policy Forum, hosted a public workshop that examined how genomic data are used in health care, outside of the traditional settings for clinical genetics. The workshop identified opportunities for advancement of precision health care delivery. The event also explored how patients, clinicians, and payers assess and act upon the risks and benefits of genomic screening and diagnostic testing. Discussions focused on strategies to ensure that genomic applications are responsibly and equitably adopted to benefit populations as well as individuals over time. This Proceedings of a Workshop summarizes content from the event.
Keywords: Health and Medicine

Toward Sequencing and Mapping of RNA Modifications: Proceedings of a Workshop–in Brief - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2023)
One strategy cells use for regulation is modifying proteins, DNA, and RNA to control their structure, function, and stability. For years, research has focused on the reversible modifications to proteins and DNA. However, RNA can also be highly modified, and more than 170 types of modification to RNA have been identified so far. Current methods for mapping and sequencing RNA and its modifications - also known as the epitranscriptome - are limited, partly because available sequencing technologies can detect only a small number of them. This limits the understanding of different molecular processes and leaves a gap in knowledge related to human diseases and disorders. To address these limitations and develop a roadmap for the sequencing of RNA with the epitranscriptome, the National Academies of Sciences, Engineering, and Medicine convened an ad hoc committee to provide a consensus report. A workshop held on March 14-15, 2023 was one part of an information-gathering effort by the committee and is summarized in this proceedings.
Keywords: Biology and Life Sciences

Evolution of Translational Omics: Lessons Learned and the Path Forward - Institute of Medicine (The National Academies Press, 2012)
Technologies collectively called omics enable simultaneous measurement of an enormous number of biomolecules; for example, genomics investigates thousands of DNA sequences, and proteomics examines large numbers of proteins. Scientists are using these technologies to develop innovative tests to detect disease and to predict a patient's likelihood of responding to specific drugs. Following a recent case involving premature use of omics-based tests in cancer clinical trials at Duke University, the NCI requested that the IOM establish a committee to recommend ways to strengthen omics-based test development and evaluation. This report identifies best practices to enhance development, evaluation, and translation of omics-based tests while simultaneously reinforcing steps to ensure that these tests are appropriately assessed for scientific validity before they are used to guide patient treatment in clinical trials.
Keywords: Biology and Life Sciences; Health and Medicine

Human Genome Editing: Science, Ethics, and Governance - National Academy of Sciences; National Academy of Medicine; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2017)
Genome editing is a powerful new tool for making precise alterations to an organism's genetic material. Recent scientific advances have made genome editing more efficient, precise, and flexible than ever before. These advances have spurred an explosion of interest from around the globe in the possible ways in which genome editing can improve human health. The speed at which these technologies are being developed and applied has led many policymakers and stakeholders to express concern about whether appropriate systems are in place to govern these technologies and how and when the public should be engaged in these decisions. Human Genome Editing considers important questions about the human application of genome editing including: balancing potential benefits with unintended risks, governing the use of genome editing, incorporating societal values into clinical applications and policy decisions, and respecting the inevitable differences across nations and cultures that will shape how and whether to use these new technologies. This report proposes criteria for heritable germline editing, provides conclusions on the crucial need for public education and engagement, and presents 7 general principles for the governance of human genome editing.
Keywords: Health and Medicine

Improving the Efficiency and Effectiveness of Genomic Science Translation: Workshop Summary - Institute of Medicine (The National Academies Press, 2014)
The process for translating basic science discoveries into clinical applications has historically involved a linear and lengthy progression from initial discovery to preclinical testing, regulatory evaluation and approval, and, finally, use in clinical practice. The low rate of translation from basic science to clinical application has been a source of frustration for many scientists, clinicians, investors, policy makers, and patients who hoped that investments in research would result in improved products and processes for patients. Some feel that the anticipated deliverables from the Human Genome Project have not yet materialized, and although understanding of human health and disease biology has increased, there has not been a concomitant increase in the number of approved drugs for patients over the past 10 years. Improving the Efficiency and Effectiveness of Genomic Science Translation is the summary of a workshop convened by the Institute of Medicine Roundtable on Translating Genomic-Based Research for Health in December 2012 to explore ways to improve the efficiency and effectiveness of the translation of genomic science to clinical practice. The workshop convened academic researchers, industry representatives, policy makers, and patient advocates to explore obstacles to the translation of research findings to clinical practice and to identify opportunities to support improvement of the early stages of the process for translation of genetic discoveries. This report discusses the realignment of academic incentives, the detection of innovative ways to fund translational research, and the generation or identification of alternative models that accurately reflect human biology or disease to provide opportunities to work across sectors to advance the translation of genomic discoveries.
Keywords: Health and Medicine

Direct-to-Consumer Genetic Testing: Summary of a Workshop - Institute of Medicine; National Research Council (The National Academies Press, 2011)
Today, scores of companies, primarily in the United States and Europe, are offering whole genome scanning services directly to the public. The proliferation of these companies and the services they offer demonstrate a public appetite for this information and where the future of genetics may be headed; they also demonstrate the need for serious discussion about the regulatory environment, patient privacy, and other policy implications of direct-to-consumer (DTC) genetic testing. Rapid advances in genetic research already have begun to transform clinical practice and our understanding of disease progression. Existing research has revealed a genetic basis or component for numerous diseases, including Parkinson's disease, Alzheimer's disease, diabetes, heart disease, and several forms of cancer. The availability of the human genome sequence and the HapMap, plummeting costs of high-throughput screening, and increasingly sophisticated computational analyses have led to an explosion of discoveries of linkages between patterns of genetic variation and disease susceptibility. While this research is by no means a straight path toward better public health, improved knowledge of the genetic linkages has the potential to change fundamentally the way health professionals and public health practitioners approach the prevention and treatment of disease. Realizing this potential will require greater sophistication in the interpretation of genetic tests, new training for physicians and other diagnosticians, and new approaches to communicating findings to the public. As this rapidly growing field matures, all of these questions require attention from a variety of perspectives. To discuss some of the foregoing issues, several units of the National Academies held a workshop on August 31 and September 1, 2009, to bring together a still-developing community of professionals from a variety of relevant disciplines, to educate the public and policy-makers about this emerging field, and to identify issues for future study. The meeting featured several invited presentations and discussions on the many technical, legal, policy, and ethical questions that such DTC testing raises, including: (1) overview of the current state of knowledge and the future research trajectory; (2) shared genes and emerging issues in privacy; (3) the regulatory framework; and (4) education of the public and the medical community.
Keywords: Health and Medicine

Genome-Based Diagnostics: Demonstrating Clinical Utility in Oncology: Workshop Summary - Institute of Medicine (The National Academies Press, 2013)
Genome-Based Diagnostics: Demonstrating Clinical Utility in Oncology is the summary of a workshop convened in May 2012 by the Roundtable on Translating Genomic-Based Research for Health and the Center for Medical Technology Policy of the Institute of Medicine to foster the identified need for further sustained dialogue between stakeholders regarding the clinical utility of molecular diagnostics. The workshop brought together a wide range of stakeholders, including patients, health care providers, policy makers, payers, diagnostic test developers, researchers, and guideline developers, to identify the challenges and opportunities in advancing the development and use of molecular diagnostic tests designed to guide the treatment and management of patients with cancer. The sequencing of the human genome has greatly accelerated the process of linking specific genetic variants with disease. These findings have yielded a rapidly increasing number of molecular diagnostic tests designed to guide disease treatment and management. Many of these tests are aimed at determining the best treatments for specific forms of cancer, making oncology a valuable testing ground for the use of molecular diagnostic tests in medicine in general. Nevertheless, many questions surround the clinical value of molecular diagnostic tests, and their acceptance by clinicians, payers, and patients has been unpredictable. A major limiting factor for the use of these tests has been the lack of clear evidence of clinical utility. Genome-Based Diagnostics assesses the evidentiary requirements for clinical utility of molecular diagnostics used to guide treatment decisions for patients with cancer; discusses methodologies related to demonstrating these evidentiary requirements that meet the needs of all stakeholders; and considers innovative, sustainable research collaborations for generating evidence of clinical utility involving multiple stakeholders.
Keywords: Health and Medicine

The Science and Applications of Microbial Genomics: Workshop Summary - Institute of Medicine (The National Academies Press, 2013)
Over the past several decades, new scientific tools and approaches for detecting microbial species have dramatically enhanced our appreciation of the diversity and abundance of the microbiota and its dynamic interactions with the environments within which these microorganisms reside. The first bacterial genome was sequenced in 1995 and took more than 13 months of work to complete. Today, a microorganism's entire genome can be sequenced in a few days. Much as our view of the cosmos was forever altered in the 17th century with the invention of the telescope, these genomic technologies, and the observations derived from them, have fundamentally transformed our appreciation of the microbial world around us. On June 12 and 13, 2012, the Institute of Medicine's (IOM's) Forum on Microbial Threats convened a public workshop in Washington, DC, to discuss the scientific tools and approaches being used for detecting and characterizing microbial species, and the roles of microbial genomics and metagenomics to better understand the culturable and unculturable microbial world around us. Through invited presentations and discussions, participants examined the use of microbial genomics to explore the diversity, evolution, and adaptation of microorganisms in a wide variety of environments; the molecular mechanisms of disease emergence and epidemiology; and the ways that genomic technologies are being applied to disease outbreak trace back and microbial surveillance. Points that were emphasized by many participants included the need to develop robust standardized sampling protocols, the importance of having the appropriate metadata, data analysis and data management challenges, and information sharing in real time. The Science and Applications of Microbial Genomics summarizes this workshop.
Keywords: Biology and Life Sciences; Health and Medicine; Conflict and Security Issues

Mapping and Sequencing the Human Genome - National Research Council (The National Academies Press, 1988)
There is growing enthusiasm in the scientific community about the prospect of mapping and sequencing the human genome, a monumental project that will have far-reaching consequences for medicine, biology, technology, and other fields. But how will such an effort be organized and funded? How will we develop the new technologies that are needed? What new legal, social, and ethical questions will be raised? Mapping and Sequencing the Human Genome is a blueprint for this proposed project. The authors offer a highly readable explanation of the technical aspects of genetic mapping and sequencing, and they recommend specific interim and long-range research goals, organizational strategies, and funding levels. They also outline some of the legal and social questions that might arise and urge their early consideration by policymakers.
Keywords: Biology and Life Sciences

Heritable Human Genome Editing - National Academy of Medicine; National Academy of Sciences (The National Academies Press, 2020)
Heritable human genome editing - making changes to the genetic material of eggs, sperm, or any cells that lead to their development, including the cells of early embryos, and establishing a pregnancy - raises not only scientific and medical considerations but also a host of ethical, moral, and societal issues. Human embryos whose genomes have been edited should not be used to create a pregnancy until it is established that precise genomic changes can be made reliably and without introducing undesired changes - criteria that have not yet been met, says Heritable Human Genome Editing. From an international commission of the U.S. National Academy of Medicine, U.S. National Academy of Sciences, and the U.K.'s Royal Society, the report considers potential benefits, harms, and uncertainties associated with genome editing technologies and defines a translational pathway from rigorous preclinical research to initial clinical uses, should a country decide to permit such uses. The report specifies stringent preclinical and clinical requirements for establishing safety and efficacy, and for undertaking long-term monitoring of outcomes. Extensive national and international dialogue is needed before any country decides whether to permit clinical use of this technology, according to the report, which identifies essential elements of national and international scientific governance and oversight.
Keywords: Health and Medicine; Biology and Life Sciences

The Genomic Revolution: Unveiling the Unity of Life - Michael Yudell; Robert DeSalle (The National Academies Press, 2002)
Keywords: Explore Science; Health and Medicine; Biology and Life Sciences

Third International Summit on Human Genome Editing: Expanding Capabilities, Participation, and Access: Proceedings of a Workshop—in Brief - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2023)
On March 6-8, 2023, at the Francis Crick Institute in London, the UK Royal Society and Academy of Medical Sciences, the U.S. National Academy of Sciences and National Academy of Medicine, and UNESCO-The World Academy of Sciences held the Third International Summit on Human Genome Editing. A follow-up to earlier international summits held in Washington, DC, in 2015 and in Hong Kong in 2018, the third summit examined scientific advances that have occurred since the previous summits and the need for global dialogue and collaboration on the safe and ethical application of human genome editing. The first two days of the summit focused largely on somatic human genome editing, where the cells being altered are non-reproductive cells - as a result genetic changes cannot be passed on to future generations. The third day of the summit broadened the discussion to include heritable human genome editing, in which genetic changes could be passed on to descendants. This publication highlights the presentations and discussion of the event.
Keywords: Biology and Life Sciences

The Common Thread: A Story of Science, Politics, Ethics, and the Human Genome - John Sulston; Georgina Ferry (The National Academies Press, 2002)
The world was agog when scientists made the astounding announcement that they had successfully sequenced the human genome. Few contributed so directly to this feat as John Sulston. This is his personal account of one of the largest international scientific operations ever undertaken. It was a momentous occasion when British scientist John Sulston embarked on the greatest scientific endeavor of our times: the sequencing of the Human Genome. In The Common Thread, Sulston takes us behind the scenes for an in-depth look at the controversial story behind the headlines. The accomplishments and the setbacks—along with the politics, personalities, and ethics—that shaped the research are frankly explored by a central figure key to the project. From the beginning, Sulston fervently proclaimed his belief in the free and open exchange of the scientific information that would emerge from the project. Guided by these principles, The Human Genome Project was structured so that all the findings were public, encouraging an unparalleled international collaboration among scientists and researchers. Then, in May 1998, Craig Venter announced that he was quitting the Human Genome Project—with plans to head up a commercial venture launched to bring out the complete sequence three years hence, but marketed in a proprietary database. Venter’s intentions, clearly anathema to Sulston and the global network of scientists working on the Project, marked the beginning of a dramatic struggle to keep the human genome in the public domain. More than the story of human health versus corporate wealth, this is an exploration of the very nature of a scientific quest for discovery. Infused with Sulston’s own enthusiasm and excitement, the tale unfolds to reveal the scientists who painstakingly turn the key that will unlock the riddle of the human genome. We are privy to the joy and exuberance of success as well as the stark disappointments posed by inevitable failures. It is truly a wild and wonderful ride. The Common Thread is at once a compelling history and an impassioned call for ethical responsibility in scientific research. As the boundaries between science and big business increasingly blur, and researchers race to patent medical discoveries, the international community needs to find a common protocol for the protection of the wider human interest. This extraordinary enterprise is a glimpse of our shared human heritage, offering hope for future research and a fresh outlook on our understanding of ourselves.
Keywords: Explore Science; Biography and Autobiography